2007
DOI: 10.1038/nature06006
|View full text |Cite
|
Sign up to set email alerts
|

The JAZ family of repressors is the missing link in jasmonate signalling

Abstract: Jasmonates are essential phytohormones for plant development and survival. However, the molecular details of their signalling pathway remain largely unknown. The identification more than a decade ago of COI1 as an F-box protein suggested the existence of a repressor of jasmonate responses that is targeted by the SCF(COI1) complex for proteasome degradation in response to jasmonate. Here we report the identification of JASMONATE-INSENSITIVE 3 (JAI3) and a family of related proteins named JAZ (jasmonate ZIM-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

68
2,411
6
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,004 publications
(2,542 citation statements)
references
References 43 publications
68
2,411
6
12
Order By: Relevance
“…Recently, it was shown that MYC2, a key transcriptional activator of jasmonate responses in Arabidopsis, interacts with the JAZ family of transcriptional repressors (Chini et al, 2007;Thines et al, 2007). The JAZ proteins are members of the ZIM family of TFs and interact with another central regulator of JA signaling, the F box protein COI1 (Chini et al, 2007;Thines et al, 2007). We have found at least 13 ZIMs in tobacco (Table I), and there are apparent homologs of the complete COI1/JAZ1/ Figure 3.…”
Section: The Bhlh Familymentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, it was shown that MYC2, a key transcriptional activator of jasmonate responses in Arabidopsis, interacts with the JAZ family of transcriptional repressors (Chini et al, 2007;Thines et al, 2007). The JAZ proteins are members of the ZIM family of TFs and interact with another central regulator of JA signaling, the F box protein COI1 (Chini et al, 2007;Thines et al, 2007). We have found at least 13 ZIMs in tobacco (Table I), and there are apparent homologs of the complete COI1/JAZ1/ Figure 3.…”
Section: The Bhlh Familymentioning
confidence: 95%
“…The phylogenetic tree identifies possible tobacco homologs of key regulators of light responses, such as the PIF/ PILs (subgroup E), and jasmonate responses, such as AtMYC2/jin1/jai1 (subgroup N). Recently, it was shown that MYC2, a key transcriptional activator of jasmonate responses in Arabidopsis, interacts with the JAZ family of transcriptional repressors (Chini et al, 2007;Thines et al, 2007). The JAZ proteins are members of the ZIM family of TFs and interact with another central regulator of JA signaling, the F box protein COI1 (Chini et al, 2007;Thines et al, 2007).…”
Section: The Bhlh Familymentioning
confidence: 99%
“…These data show that JA biosynthesis (catalyzed by AOS) is necessary and sufficient for trichome induction. COI1 encodes an F-box subunit of the SCF E3 ubiquitin ligase complex (SCF COI1 ) and is an essential component of the JA receptor (Xie et al, 1998;Chini et al, 2007;Thines et al, 2007;Katsir et al, 2008). Like aos, coi1-1 did not show increased trichomes in response to wounding (Fig.…”
Section: Endogenous Ja Regulates Trichome Patterningmentioning
confidence: 99%
“…Wounded tissue rapidly activates JA biosynthesis (Glauser et al, 2008), and increased JA triggers the SKP1/Cullin/F-box E3 ubiquitin ligase complex containing the F-box subunit CORONATINE INSENSITIVE1 (SCF COI1 ) to degrade the repressors of JA signaling -the JASMONATE-ZIM (JAZ) family proteins -by the ubiquitin/26S-proteasome pathway (Chini et al, 2007;Thines et al, 2007). In addition to their local synthesis and action, JAs also move systemically via vascular strands to transmit wound signals to distal tissues (Li et al, 2002;Thorpe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…repressor와 결합한다 (Chini et al 2007;Thines et al 2007;Yan et al 2007;Pauwels et al 2010). 그 결과로 MYC2, MYC3, MYC4를 포함한 JA 반응에 필수적인 다양한 하부 전사인자들이 활성 화된다 (Cheng et al 2011;Fernández-Calvo et al 2011;Niu et al 2011).…”
unclassified